2021
DOI: 10.18699/vj21.015
|View full text |Cite
|
Sign up to set email alerts
|

Production of subtilisin proteases in bacteria and yeast

Abstract: In this review, we discuss the progress in the study and modif ication of subtilisin proteases. Despite longstanding applications of microbial proteases and a large number of research papers, the search for new protease genes, the construction of producer strains, and the development of methods for their practical application are still relevant and important, judging by the number of citations of the research articles on proteases and their microbial producers. This enzyme class represents the largest share of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…A further increase in temperature to 50°C resulted in the formation of considerable amount of biofilm by SH-19. This is a well-known phenomenon and occurs probably owing to the diversity of optimal temperatures of the isolates (Rozanov et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A further increase in temperature to 50°C resulted in the formation of considerable amount of biofilm by SH-19. This is a well-known phenomenon and occurs probably owing to the diversity of optimal temperatures of the isolates (Rozanov et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Due to a combination of characteristics such as thermostability, wide range of pH compatibility, and broad specificity, family S8 or more commonly known as subtilisin family has turned out to be one of the most well‐known classes of proteases. Subtilisin is generally isolated from a wide range bacterial sources of the Bacillus genus such as Bacillus subtilis, B. amyloliquefaciens, B. licheniformis, B. lentus, B. clausii , and B. alkalophilus 1 . Isolation of subtilisin‐like protease from microorganisms are also not limited to species such as Thermococcus kodakarensis and Thermoactinomyces vulgaris .…”
Section: Subtilisinmentioning
confidence: 99%
“…Subtilisin is generally isolated from a wide range bacterial sources of the Bacillus genus such as Bacillus subtilis, B. amyloliquefaciens, B. licheniformis, B. lentus, B. clausii, and B. alkalophilus. 1 Isolation of subtilisin-like protease from microorganisms are also not limited to species such as Thermococcus kodakarensis and Thermoactinomyces vulgaris. At first, it is suggested that all Ser peptidases would be homologous to chymotrypsin.…”
Section: Subtilisinmentioning
confidence: 99%
See 2 more Smart Citations